Effects of Transglutaminase on the Gel Properties of Indonesian Catfish Surimi Using Response Surface Methodology - Royanti, Ida; Nandyawati, Dewi; Putri, Renny Primasari Gustia; Kusumasmarawati, Ambar Dwi; Abidin, Kharis Yohan; Pradiva, Molina Indah; Dewi, Rizky Aulia Prasasti; Gebrina, Amanda Dwi; Purwoto, Heri; Widyasti, Erma (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
Surimi is a myofibrillar fish protein, extracted mainly from marine fish, which is commonly used to produce fish balls, crab imitation products, and various other seafood substitutes. However, finding an alternative fish from freshwater, such as freshwater catfish, is important, although its drawbacks include low gel strength and water-holding capacity. To address this problem, transglutaminase addition can maintain the surimi quality. This study aimed to improve catfish surimi characteristics by optimizing surimi production with various transglutaminase concentrations and incubation times. It used Response Surface Methodology (RSM) with Central Composite Design (CCD) to evaluate the effect of Enzyme Concentration and Incubation Time. The result showed that the catfish surimi gel strength, chewiness, whiteness, and water-holding capacity were respectively 927.513 g.cm, 3,747.18 g, 79.95 %, and 91.37 %. It was obtained by the optimum condition of surimi production with the addition of 0.85 % w/w transglutaminase and an incubation time of 36 minutes. The overall study provides insight for surimi producers to maintain surimi characteristics from freshwater fish, such as catfish.